Exosomes in Human Immunodeficiency Virus Type I Pathogenesis: Threat or Opportunity? - Teow, Sin Yeang; Nordin, Alif Che; Ali, Syed A.; Khoo, Alan Soo Beng (Hindawi Publishing Corporation, 2016)
Nanometre-sized vesicles, also known as exosomes, are derived from endosomes of diverse cell types and present in multiple biological fluids. Depending on their cellular origins, the membrane-bound exosomes packed a variety of functional proteins and RNA species. These microvesicles are secreted into the extracellular space to facilitate intercellular communication. Collective findings demonstrated that exosomes fromHIV-infected subjects sharemany commonalities withHuman ImmunodeficiencyVirus Type I (HIV-1) particles in terms of proteomics and lipid profiles. These observations postulated that HIV-resembled exosomes may contribute to HIV pathogenesis. Interestingly, recent reports illustrated that exosomes from body fluids could inhibit HIV infection, which then bring up a new paradigm for HIV/AIDS therapy. Accumulative findings suggested that the cellular origin of exosomes may define their effects towards HIV-1. This review summarizes the two distinctive roles of exosomes in regulating HIV pathogenesis. We also highlighted several additional factors that govern the exosomal functions. Deeper understanding on how exosomes promote or abate HIV infection can significantly contribute to the development of new and potent antiviral therapeutic strategy and vaccine designs.